Chaucer and the Poets : An Essay on Troilus and Criseyde - Wetherbee, Winthrop (Cornell University Press, 1984)
In this sensitive reading of Chaucer$1 (Bs Troilus and Criseyde, Winthrop Wetherbee redefines the nature of Chaucer$1 (Bs poetic vision. Using as a starting point Chaucer$1 (Bs profound admiration for the achievement of Dante and the classical poets, Wetherbee sees the Troilus as much more than a courtly treatment of an event in ancient history$1 (Bit is, he asserts, a major statement about the poetic tradition from which it emerges. Wetherbee demonstrates the evolution of the poet-narrator of the Troilus, who begins as a poet of romance, bound by the characters$1 (Blimited worldview, but who in the end becomes a poet capable of realizing the tragic and ultimately the spiritual implications of his story. s
English
Keywords: classical literature; Vergil; Dante Alighieri; Troilus and Criseyde; Statius; medieval literature; (alternate spelling of "Vergil" Ovid; Geoffrey Chaucer; Roman de la rose